Esse obscuro objeto incômodo: o “cinema direto” nas reflexões cubanas (e latino-americanas) sobre o documentário - Núñez, Fabián (2019)
This article aims to weave reflections on how non-fiction cinema was conceived in Cuba in the 1960s and 1970s, in particular, the debate around the "direct cinema". Thus, from the analysis of the Cuban documentary conception I aim to reflect on its role in the construction of a formative speech about the identity of the revolutionary Cuban cinematography.